(untitled) (Heritage, 2023)
The Russian-Georgian five-day war represents not only an extremely interesting military phenomenon, but also sheds light on the challenging corridors of the complex geopolitical framework in the South Caucasus region. Although this five-day war is relatively often mentioned in the domestic public during various military and political analyses, it is noticeable that there is no adequate fund of scientific papers and other professional analyzes that would follow this dynamic and level of interest. Certain events of a complex structure and character, which certainly includes a war, even a five-day one, require a certain time distance and passage of time, in order to create the conditions to draw objective conclusions, which would be useful in both scientific and social meaning. Although at that time this war seemed, conditionally speaking, as a fairly simple and successful operation of the Russian armed forces, it actually brought to the surface all the anomalies, not only of the Russian army, but also of the Russian society as a whole, with its multi-layered analysis. This contributed to the Russian state leadership making important decisions and making certain systemic changes, which brought progress to the Russian side, and added worries to the opponents. From the characteristics of this war, many other countries can also draw certain experiences, primarily for the most effective protection of their sovereignty and territorial integrity.